An integrated system for real-time detection of stiff masses with a single compression - Fahmy, A.S.; Krieger, A.; Osman, N.F. (IEEE transactions on biomedical engineering, 2006)
An integrated system is proposed for real-time imaging of tissue deformation in response to externally applied mechanical compression. The purpose of the system is to noninvasively detect tissue lesions based on their stiffness. The method includes applying external compression to the examined subject and acquiring magnetic resonance strain-encoded images using a real-time pulse sequence. In the proposed system, only a single compression is necessary to obtain a two-dimensional map of tissue deformation in a slice, eliminating the need for a complicated compressing device. The system was built and validated using phantom experiments.